2016
DOI: 10.1002/lary.26361
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing mortality in pediatric tracheostomy patients

Abstract: 4 Laryngoscope, 127:1701-1706, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
87
1
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 22 publications
16
87
1
7
Order By: Relevance
“…These findings were not related to higher rates of prematurity, lower gestational weights, or younger gestational ages in this group. The findings of increased mortality in infants with CHD are similar to other studies evaluating tracheostomy in pediatric patients of all ages with cardiac disease . For example, Funamura et al reported 27.5% mortality in children with CHD at various periods of follow‐up, which was significantly higher than patients without cardiac disease.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These findings were not related to higher rates of prematurity, lower gestational weights, or younger gestational ages in this group. The findings of increased mortality in infants with CHD are similar to other studies evaluating tracheostomy in pediatric patients of all ages with cardiac disease . For example, Funamura et al reported 27.5% mortality in children with CHD at various periods of follow‐up, which was significantly higher than patients without cardiac disease.…”
Section: Discussionsupporting
confidence: 82%
“…In comparison, older children with tracheostomies are more likely to have underlying medical complexities, which influence both need for tracheostomy placement, and impact mortality. For example, in a cohort of 513 patients, Funamura et al reported 16.6% mortality; however, this group included patients with cystic fibrosis, lung transplant, and oncologic diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall 30‐day mortality for all patients was 4.24%, which is similar to previously published short‐term outcomes but less than previously published longer term outcomes, which were 8.9% to 29% . This difference is likely secondary to the morbid and chronic nature of the underlying etiology requiring the tracheostomy.…”
Section: Discussionsupporting
confidence: 75%